1988
DOI: 10.1136/jech.42.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma among teenagers attending school in Tahiti.

Abstract: SUMMARY The prevalence ofasthma was studied in 6731 adolescents (average age 13.5 years, 48.6% boys) attending school in three towns of the isle of Tahiti, according to the ethnic origin of both parents. The pupils completed a self-administered questionnaire in class; 14.3% gave an affirmative answer to the question "Have you ever had attacks of asthma?" (cumulative prevalence). That prevalence was 11.4% in the Europeans, 13.7% in the Chinese, 13.8% in the Polynesians, 15.3% in those whose parents were "halves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…To our knowledge, there have been no previous surveys of allergic rhinoconjunctivitis or eczema in the Pacific. As noted above, of the few studies of asthma prevalence (4–6) conducted in the Pacific prior to the ISAAC study, none were comparable in either methodology or used similar instruments. Waite et al used a self‐completed questionnaire (6) and reported a prevalence of 11.0% among 706 Tokelauan children aged 0–14 years in Tokelau compared with 25.3% of the 1160 Tokelauan children seen in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, there have been no previous surveys of allergic rhinoconjunctivitis or eczema in the Pacific. As noted above, of the few studies of asthma prevalence (4–6) conducted in the Pacific prior to the ISAAC study, none were comparable in either methodology or used similar instruments. Waite et al used a self‐completed questionnaire (6) and reported a prevalence of 11.0% among 706 Tokelauan children aged 0–14 years in Tokelau compared with 25.3% of the 1160 Tokelauan children seen in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Waite et al used a self‐completed questionnaire (6) and reported a prevalence of 11.0% among 706 Tokelauan children aged 0–14 years in Tokelau compared with 25.3% of the 1160 Tokelauan children seen in New Zealand. Another self‐administered questionnaire study of 6731 adolescent schoolchildren (average age 13.5 years) in Tahiti in French Polynesia reported that 14.3% gave an affirmative answer to the question ‘Have you ever had attacks of asthma?’; the prevalence was 11.4% among Europeans, 13.7% among Chinese, 13.8% among Polynesians, and 15.3% among children of mixed Polynesia–European ancestry (4). Thus, Liard et al (4) found no evidence for any differences in asthma prevalence between the three main ethnic groups participating (European, Chinese, Polynesian).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma is not the only cause of attacks of breathlessness and wheezing, yet this symptom complex is commonly used as a diagnostic criterion for asthma in epidemiological studies (26). Asthma is not the only cause of attacks of breathlessness and wheezing, yet this symptom complex is commonly used as a diagnostic criterion for asthma in epidemiological studies (26).…”
Section: Discussionmentioning
confidence: 99%